2012
DOI: 10.1097/aln.0b013e3182655f9f
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Gr-1+Leukocytes in Postincisional Nociceptive Sensitization and Inflammation

Abstract: Background Neutrophils are one of the predominant immune cells migrating to surgical wound edges initially. They produce mediators both associated with supporting (interleukin [IL]-1β, C5a) and reducing (opioid peptides) pain. Studies demonstrate neutrophil depletion/blockade reduces nociceptive sensitization after nerve injury and carrageenan administration, but enhance sensitization in Complete Freund's Adjuvant inflammation. This research identifies the contribution of infiltrating neutrophils to incisional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 52 publications
(67 reference statements)
1
41
1
1
Order By: Relevance
“…Neutrophils secrete many proinflammatory mediators but also produce opioid peptides that might reduce pain. This dichotomy is evident in the literature, with studies showing that these cells can increase (53)(54)(55) or decrease (56, 57) hypersensitivity, whereas others have shown no effect (58,59) in various models of inflammatory pain. Our results suggest a lack of any major contribution for these cells to pain, at least under our conditions and in other models in which clear depletion was demonstrated.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neutrophils secrete many proinflammatory mediators but also produce opioid peptides that might reduce pain. This dichotomy is evident in the literature, with studies showing that these cells can increase (53)(54)(55) or decrease (56, 57) hypersensitivity, whereas others have shown no effect (58,59) in various models of inflammatory pain. Our results suggest a lack of any major contribution for these cells to pain, at least under our conditions and in other models in which clear depletion was demonstrated.…”
Section: Discussionmentioning
confidence: 90%
“…Two studies (54, 60) used a similar antibody-mediated neutrophil depletion paradigm in an incisional wound. Sahbaie et al (54) found only a minor effect in thermal latency and no change in mechanical threshold. Carreira et al, meanwhile, saw a dramatic reduction in mechanical hypersensitivity with antibody treatment, but this could have been a result of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…3C and 5). Sahbaie et al 22 previously reported that the depletion of Gr-1 + neutrophils in the incised paw, associated with IL-1β levels half those of the controls 24 hours after incision, did not alter the magnitude or duration of mechanical hypersensitivity, indicating that the increase in Gr-1 + PMNs and expression of IL-1β in peripheral tissue might contribute less to the development of postoperative pain.…”
Section: Discussionmentioning
confidence: 94%
“…26 The method described by Hargreaves et al modified for mice was used to determine heat sensitivity. [27][28][29] After acclimation on a temperature-controlled glass platform (23.5°C) in a plastic enclosure with the same dimensions as above, the hindpaw was presented with a beam of light from the heat source. To prevent tissue damage, a 15-second cutoff was used.…”
Section: Nociceptive Assaysmentioning
confidence: 99%